1997
DOI: 10.1111/j.1469-7793.1997.259bc.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental rehearsal of motor tasks recruits α‐motoneurones but fails to recruit human fusimotor neurones selectively

Abstract: As mental rehearsal of movements activates multiple cortical areas associated with movement, we assessed whether this increases fusimotor drive and whether enhanced muscle spindle activity could contribute to the improvement in skill that accompanies mental rehearsal. Microneurographic recordings were made from six muscle spindle afferents innervating extensor muscles in the forearm or tibialis anterior, which were selected because their discharge increased during very weak contractions. Activity was monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 28 publications
6
68
0
3
Order By: Relevance
“…16,17 Alternatively, mental rehearsal of a particular motor skill may partially activate the descending corticospinal pathway, the spinal machinery, and effector muscles. 18,19 In line with this hypothesis are the observations that spinal circuits are activated by transcranial magnetic stimulation in a similar manner during motor imagery and motor execution. 20-27 This finding, however, is challenged by other studies, showing modulation of the motor cortical excitability without evoking descending volleys to the spinal cord.…”
Section: Neural Substrates Of Mental Practicesupporting
confidence: 61%
“…16,17 Alternatively, mental rehearsal of a particular motor skill may partially activate the descending corticospinal pathway, the spinal machinery, and effector muscles. 18,19 In line with this hypothesis are the observations that spinal circuits are activated by transcranial magnetic stimulation in a similar manner during motor imagery and motor execution. 20-27 This finding, however, is challenged by other studies, showing modulation of the motor cortical excitability without evoking descending volleys to the spinal cord.…”
Section: Neural Substrates Of Mental Practicesupporting
confidence: 61%
“…This will require a complete description of the state of the motor system, which seems difficult with the presently available techniques. For example, standard EMG recordings may miss the activity of deep muscular fibers; the degree of activity of muscle spindle afferents remains unknown [32]. This approach should bridge the gap between the study of cognitive phenomena such as the covert states of action generation, thought to be possible only in man, and the detailed study of the underlying neural mechanisms accessible only in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Even without changes in the excitability of motoneurons and interneurons, the effect of an external stretch would thus be magnified and could trigger a stretch reflex during motor imagery. However, this is not likely to happen, because Gandevia et al (1997) reported no change in spindle afferent discharge (and therefore the ␥-motor system) during motor imagery. In contrast, their results showed increased motoneuronal activity and reflex excitability.…”
Section: Potential Mechanisms For Enhanced Spinal Excitabilitymentioning
confidence: 99%
“…First, as indicated above, it could be because of subthreshold activation of motoneurons during motor imagery (cf. Gandevia et al, 1997). Because of the existence of direct corticomotoneuronal connections, especially for finger muscles (Porter and Lemon, 1993), it is possible that the excitability of spinal motoneurons is modulated directly by the motor cortex outflow.…”
Section: Potential Mechanisms For Enhanced Spinal Excitabilitymentioning
confidence: 99%